FENOMENA PERILAKU MEMILIH PADA PILGUB JATENG 2013 - Utomo, Susilo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aims to explain the victory of the pair Ganjar Pranowo - Heru Sujatmoko (GaGah) in Pilgub jateng 2013 from the perspective of voting behavior. Is the figure or factor that determines victory party machine GaGah couple ? The research method used was a mixed method research, using depth interviews with key figures GaGah successful team. The results showed a victory GaGah couple in Pilgub jateng 2013 in because the pattern of voting behavior-oriented figure which represents the aspirations and expectations poles party (PDI-Perjuangan). PDI-Perjuangan which is the bearer party GaGah couple is a political machine that has a strong social basestructured and have a social network to the grassroots level.